PENGARUH ALOE VERA PADA TRANSMITANSI ULTRASONIK GEL KARBOMER 940 - M. Rosyid Ridlo (Teknoin, 2016)
On examination using USG ( ultrasonography), gel carbomer 940 applied on body surface has role as acoustic coupling agent between USG probe and body surface. The function of this gel is to transmit ultrasonics wave from probe to body without resisted by the air. Gel carbomer 940 is a non biodegradable matter. For decreasing the content of non biodegradable part of carbomer 940, in this research, the extract of aloe vera was added into gel carbomer 940. To know the efficiency of ultrasonics energy tramsmitted to the body, transmitansi coefficient measurement is required.. Transmitansi coefficient can be calculated from ultrasonics velocity value in the gel. The velocity measurement use transmit time method with equipment the ultrasonics thickness gauge AR860 connected to osciloscope. Examanation of the coefficient was carried out in first and 12 th week. The results indicated the acoustic impedance and the transmitansi coefficient decreased by adding of aloevera content. However at 12 th week the influence of aloe vera relatively did not give effect to the gel carbomer transmittance.